ABR: a novel inducer of transcription factor C/EBPα, contributes to myeloid differentiation and is a favorable prognostic factor in acute myeloid leukemia - Namasu, Carolina Yaeko; Katzerke, Christiane; Bräuer-Hartmann, Daniela; Wurm, Alexander Arthur; Gerloff, Dennis; Hartmann, Jens-Uwe; Schwind, Sebastian; Müller-Tidow, Carsten; Hilger, Nadja; Fricke, Stephan; Christopeit, Maximilian Erich Joachim; Niederwieser, Dietger; et al. (OncoTarget, 2017)
ABR; C/EBPα; acute myeloid leukemia; myelopoiesis; prognostic